Creative Workshop - Creative Activity of Undergraduate Students in The Process of Theatre Creation - Kušnírová Eva (Sciendo, 2019)
Within the frame of the study field of Aesthetics at Faculty of Arts Prešov University in Prešov, the students have an opportunity to acquire abilities and skills also in creative artistic activities. One of the possibilities is to participate in the creative workshops as the part of Academic Prešov Festival that is very popular with the participants. The actors of a creative workshop can experience, in a short period of time (mostly weekly), an intense creative process in which a young undergraduate student headed by a professional, in the amateur communication with a professional, can experience an unrepeatable experience of creativity, creation of theatrical work as well as the distinctive level of theatrical communication on the axis of participant-lecture-process-making-theatrical work-viewer. In this way, he discovers potential artistic, authentic, and generationally specific dispositions.